Formato, área de comedouros em tanques-rede para juvenis de tilápia do Nilo - Marengoni, N. G.; Mahl, I.; Albuquerque, D. M.; Moura, M. C.; Sanches, E. A. [UNESP]; Piana, P. A. (Cordoba University Press (UCOPress), 2017)
This study aimed to evaluate formats and areas of feeders used in cages on production performance, uniformity of lots and body indexes of Nile tilapia. 2700 juvenile tilapia with mean weight of 5.95 ± 1.23 g were used, distributed in 27 cages (0.5 x 0.5 x 1.0 m) in a completely randomized design in a factorial model, consisting of feeders with two formats (square and circular) and four areas (100, 75, 50 or 25%) and a control (feeder free) with three replicates. After 64 days, we evaluated the performance parameters of weight gain, total length, specific growth rate, survival, feed conversion and uniformity of lots. The viscerosomatic, hepatosomatic and visceral fat indexes were also evaluated. The format of feeders did not influence (p>0.05) the performance parameters of tilapia juvenile, however, the lack of a feeder area affected (p<0.05) negatively the survival of the juvenile. We observed lower values of weight gain (25.45 g) and length (11.50 cm) and higher feed conversion for fish reared in cages at absent of feeders. The feed conversion was higher (p<0.05) for fish in cages without feeder compared to the others. The format and the area of feeders did not affect (p>0.05) corporeal indexes, however, fish subjected to cages without feeders had lower (p<0.05) hepatosomatic, viscerosomatic, and visceral fat indexes. The different areas and formats feeder do not interfere in the productive performance in the juvenile phase of Nile tilapia in cages of small volume. For a better utilization of diets on the fish performance, we recomend to use, at least, one of the combinations of size and format of feeder used during cultivation in cages.
Format and size of feeders in cages for Nile tilapia juvenile
Keywords: Body indexes; Homogeneity of lots; Oreochromis niloticus; Productive performance; Tilapiculture